2020
DOI: 10.1021/acs.chemmater.0c02111
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Silica Coating of DNA Origami Nanostructures

Abstract: The DNA origami technique has emerged as one of the most versatile bottom-up nanofabrication methods due to its ability to construct well-defined complex three-dimensional nanostructures and guide assembly of functional nanoscale objects with unprecedented precision, high yields, and controlled stoichiometry. Nonetheless, limited compatibility with biologically relevant fluids and typical solvents utilized in nanofabrication often restricts applications of DNA origami-based assemblies and devices. Here we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 88 publications
0
56
0
Order By: Relevance
“…Simulations of a 2D DNA origami triangle with four or eight staple Peptoid Small protein-like polymer in which the side chains are attached to backbone nitrogen atoms, rather than to the α-carbons, as in peptides. These approaches include a coating formed through the complexation of human serum albumin (HSA) and DNA dendrites 120 (part a); coating nanostructures with dendritic DNA through hybridization to DNA handles 121 (part b); a PEGylated (where PEG is polyethylene glycol) lipid bilayer protective envelope 122 (part c); the charge-based accumulation of a poly ca tionic shell 123 (part d); an oligolysine-PEG coating 124 (part e); a coating formed through glutaraldehyde crosslinking of oligolysines 125 (part f); a bovine serum album (BSA)dendron block copolymer coating 127 (part g); a coating comprising DNA peptoids 128 (part h); and silica-based coatings 130 strands omitted from the structure, each resulting in a metastable assembly, revealed that the accessibility of the enzyme to the structure is dependent on the interconversion between these metastable states. This analysis showed that the reactivity of restriction enzymes is dependent on the steric overlap between the enzyme and the adjacent helices, thus, providing a route to designing nanostructures with higher or lower nuclease resistance.…”
Section: Mechanism Of Nuclease Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Simulations of a 2D DNA origami triangle with four or eight staple Peptoid Small protein-like polymer in which the side chains are attached to backbone nitrogen atoms, rather than to the α-carbons, as in peptides. These approaches include a coating formed through the complexation of human serum albumin (HSA) and DNA dendrites 120 (part a); coating nanostructures with dendritic DNA through hybridization to DNA handles 121 (part b); a PEGylated (where PEG is polyethylene glycol) lipid bilayer protective envelope 122 (part c); the charge-based accumulation of a poly ca tionic shell 123 (part d); an oligolysine-PEG coating 124 (part e); a coating formed through glutaraldehyde crosslinking of oligolysines 125 (part f); a bovine serum album (BSA)dendron block copolymer coating 127 (part g); a coating comprising DNA peptoids 128 (part h); and silica-based coatings 130 strands omitted from the structure, each resulting in a metastable assembly, revealed that the accessibility of the enzyme to the structure is dependent on the interconversion between these metastable states. This analysis showed that the reactivity of restriction enzymes is dependent on the steric overlap between the enzyme and the adjacent helices, thus, providing a route to designing nanostructures with higher or lower nuclease resistance.…”
Section: Mechanism Of Nuclease Resistancementioning
confidence: 99%
“… Various protective coatings have been developed to increase the nuclease resistance of DNA nanostructures. These approaches include a coating formed through the complexation of human serum albumin (HSA) and DNA dendrites 120 (part a ); coating nanostructures with dendritic DNA through hybridization to DNA handles 121 (part b ); a PEGylated (where PEG is polyethylene glycol) lipid bilayer protective envelope 122 (part c ); the charge-based accumulation of a polycationic shell 123 (part d ); an oligolysine–PEG coating 124 (part e ); a coating formed through glutaraldehyde crosslinking of oligolysines 125 (part f ); a bovine serum album (BSA)–dendron block copolymer coating 127 (part g ); a coating comprising DNA peptoids 128 (part h ); and silica-based coatings 130 (part i ). APTES, (3-aminopropyl)triethoxysilane; DMTO, dimethoxytrityloxy; LPEI, linear polyethyleneimine; Nae, N -(2-aminoethyl)glycine; Nte, N -2-(2-(2-methoxyethoxy)ethoxy)ethylglycine; TEOS, tetraethyl orthosilicate; TMAPS, N -trimethoxysilylpropyl- N , N , N -trimethylammonium chloride.…”
Section: Strategies To Modulate Nuclease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al recently showed that coating the DNA origami structures with an ultrathin layer of silica prevents the origamis from degradation and aggregation in otherwise lethal ionic solvents. [190,191] However, it was not clear if the structures were functional or modifiable after the coating. Alternatively, Gerling et al showed that at elevated temperatures and in ultrapure water, welding the thymidine groups by ultraviolet light creates additional covalent bonds that enhance the structural stability of origamis.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Tremendous efforts have been done on this end to arrange gold, silver, quantum dots, silica, and carbon nanotubes with the nanoscale precision down to sub 10 nm. [26][27][28][29][30][31][32][33][34][35][36][37] However, there is still plenty room to go toward smaller sizes of materials. The other challenge lies on arranging materials with greater diversity in their chemical composition, which is a necessary step toward the bottom-up fabrication of functional nanodevices.…”
Section: Doi: 101002/smll202103877mentioning
confidence: 99%